The immunoregulatory effects of scoparone on immune-mediated inflammatory diseases - Qiu, Feifei; Lin, Jingru; Huang, Xiaofei; Yang, Bin; Lu, Weihui; Dai, Zhenhua (Frontiers in Immunology, 2025)
Scoparone (SCO), also known as 6,7-Dimethoxycoumarin, is a naturally occurring bioactive ingredient originally derived from Chinese herb Artemisiae Scopariae Herba (Yin-Chen-Hao). Previous studies have shown that it is effective in treating some of the liver diseases. Beyond its hepatoprotective effects, an expanding body of research has underscored the immunoregulatory properties of SCO, indicating its potential therapeutic benefits for autoimmune and other inflammatory diseases. Over the past decade, significant advances have been made in understanding the mechanistic insights into its effects on immune-mediated diseases as well as liver diseases. SCO has an impact on various immune cells, including mast cells, monocytes, macrophages, neutrophils and T cells, and affects a broad range of intracellular signaling pathways, including TLR4/Myd88/NFκB, TGFβR/Smad3 and JNK/Sab/SHP-1 etc. Therefore, this review not only summarizes the immunomodulatory and therapeutic effects of SCO on immune-based inflammatory diseases (IMIDs), such as inflammatory bowel disease, osteoarthritis, allergic rhinitis, acute lung injury, type 1 diabetes and neuroinflammatory diseases etc., but also provides a comprehensive summary of its therapeutic effects on hepatic diseases, including non-alcoholic steatohepatitis, fulminant hepatic failure and hepatic fibrosis. In this review, we also include the broad impacts of SCO on intracellular signaling pathways, such as TLR4/Myd88/NFκB, TGFβR/Smad3, Nrf2/P38, JAK2/STAT3 and JNK/Sab/SHP-1 etc. Further researches on SCO may help understand its in-depth mechanisms of action and pave the way for the development of novel drugs to prevent and treat various immune-mediated inflammatory disorders as well as hepatic diseases, thereby significantly advancing its innovations and pharmaceutical applications.